2022
DOI: 10.1097/jnc.0000000000000305
|View full text |Cite
|
Sign up to set email alerts
|

Condomless Sex With Partners and Clients Among Female Sex Workers in Iran: A Systematic Review and Meta-Analysis

Abstract: Condomless sex is the most proximal risk for HIV acquisition among female sex workers (FSWs). We performed a systematic review and meta-analysis to summarize the evidence for the prevalence of condomless sex among FSWs in Iran. A random-effect metaanalysis model was used to pool the prevalence estimates and their 95% confidence intervals (CIs). The pooled prevalence of condomless sex at last sex with a paying client and a nonpaying partner was 34.23% (95% CI: 27.83-40.93) and 48.34 (95% CI: 38.43-58.32), respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Although women typically alcohol use less than men, the prevalence of alcohol use among FSWs in Iran is indeed higher than that of the general female population (Khezri et al., 2022 ). In Iran, sex work is illegal and criminalized, and sensitivities around FSWs in Iran are mainly rooted in the sociocultural, religious, and political context of Iran as a Muslim majority setting (Karamouzian et al., 2016 ; Karamouzian et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although women typically alcohol use less than men, the prevalence of alcohol use among FSWs in Iran is indeed higher than that of the general female population (Khezri et al., 2022 ). In Iran, sex work is illegal and criminalized, and sensitivities around FSWs in Iran are mainly rooted in the sociocultural, religious, and political context of Iran as a Muslim majority setting (Karamouzian et al., 2016 ; Karamouzian et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Syphilis infection was estimated at 1.7% among FSWs in China, which was 6.8 times higher than among general population women in 2017 ( 7 ). FSWs contribute significantly to STIs transmission networks through their engagement in frequent unprotected sexual activities, multiple commercial sex partners ( 8 10 ), and limited asymptomatic STIs awareness ( 11 ). An Ecuador study reported that 25.5% of FSWs had unprotected sexual activities at least once in the previous 3 months ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Societal views on sex work further restrict their access to legal aid and support, isolating them and complicating their efforts to promote safer sex. Moreover, the criminalization of sex work in various places prevents them from seeking justice for abuses and accessing health services freely, perpetuating their risk and marginalization (7)(8)(9).…”
mentioning
confidence: 99%